What is really new in triglyceride guidelines?. Issue 2 (1st April 2023) - Hussain, Aliza; Al Rifai, Mahmoud; Hermel, Melody; Slipczuk, Leandro; Virani, Salim S.
Abstract : Purpose of review: In this review, we will summarize some of the landmark clinical trials of triglyceride-lowering therapies and review updates in clinical guidelines with regards to treatment of elevated triglyceride levels. Recent findings: Accumulating evidence from epidemiologic and Mendelian randomization studies has shown that triglyceride and are causally linked to atherosclerotic cardiovascular disease (ASCVD) and contribute to atherosclerosis. However, most clinical trials evaluating use of triglyceride-lowering therapies, including fibrates, niacin and fish oils [combined eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] have not been able to demonstrate significant cardiovascular risk reduction. REDUCE-IT is the only randomized clinical trial that showed significant cardiovascular benefit with the use of icosapent ethyl esters (a purified EPA), in patients with ASCVD or diabetes with elevated risk on maximally tolerate statin. Summary: Current guidelines and expert consensus documents from multiple societies strongly endorse therapeutic lifestyle interventions to effectively lower TG as the first-line therapy for treatment of hypertriglyceridemia. Evaluation and treatment of secondary causes of hypertriglyceridemia including optimal glycaemic control is crucial. Statins lower ASCVD risk in patients with elevated triglycerides and are first-line for treatment of elevated triglyceride. In a patient with residual mild to moderate hypertriglyceridemia on maximally tolerate statin and elevated cardiovascular risk icosapent, ethyl ester may be used for further ASCVD risk reduction.